Ecosystem Urbanism: the proposition of a Green Infrastructure System in Avaré - Bruno Dalcim , Lucas; Ruivo Alves dos Santos , Iago (Technical and Scientific Journal Green Cities, 2022)
The research seeks to highlight possibilities of establishing an Urban Planning methodology that encompasses Ecosystem Green Infrastructure guidelines. From the study of the urban area of the city of Avaré - SP, it was established a broader reading of the territory where it was surveyed the meetings of the micro-watersheds to understand the origins of the city's waters. Qualitative mappings of the city of Avaré and a Macrodrainage plan developed by the Municipality of Avaré were surveyed. By overlapping the mappings, it was possible to establish an interrelationship between public spaces, green spaces, streams and rivers, and the drainage network. From this study, it was developed a Green Infrastructure System Masterplan that encompasses the entire city of Avaré.  KEY-WORDS: Green Infrastructure, Urban Drainage, Ecosystem.